In vitro pollen germination test for white rust tolerance in Brassicas - NARESH MEHTA and T.M. VARGHESE, ANJALI JAIN, H.R. DHINGRA (Indian Phytopathology, 2002)
The relationship between the responses of pollen from Brassica spp. to leachate from sporangia of the white rust pathogen (Albugo candida) and the whole plant response to the pathogen were studied. B. alba [Sinapis alba], B. carinata, B. napus and B. juncea (7 cultivars) grown in Hisar, India, in 1996 were used for the study. Sporangia leachate was prepared from infected leaves. Pollen was collected from plants and was tested for the sensitivity to the leachate by examining germination. The pollenfrom the Brassica species and cultivars showed differential sensitivity to the sporangial leachate. Pollen obtained from plants with known resistance to white rust were less affected than the pollen from susceptible plants. Pollen grains of B. carinata were most tolerant to the sporangial leachate followed by B. napus. Of the cultivars of B. juncea, Pisa Bold was the most tolerant, followed by Domo-4. It is suggested that pollen performance has a positive correlation with the known whole plant resistance to white rust.